Chapter 5: Addressing a neglected problem: Community-based management of acute malnutrition [Nourishing Millions] - Hodge, Judith; White, Jessica (2016)
SEVERE ACUTE MALNUTRITION (SAM)—extremely low weight for one’s height—is a life-threatening condition affecting mostly children under five years of age. It is caused by a combination of infection, such as diarrheal disease, and poor diets that are inadequate for nutritional needs. SAM is one of the top three nutrition-related causes of death in children under five according to the 2008 Maternal and Child Nutrition Lancet Series. A child with SAM is 11 times more likely to die than a well-nourished child. Despite the size of the problem, until the early 2000s SAM appeared to be a so-called neglected disease: little support went to large-scale treatment programs targeted toward children with SAM. Few countries-even among those with a high preva-lence of malnutrition-had a clear national pol-icy for detecting and treating SAM children.10 The development and adoption of a new approach-the community-based management of acute malnutri-tion (CMAM)-was to change the public health nutrition landscape by bringing treatment out of hospitals and into the community